Kaizen workshops for lean healthcare - Jackson, Thomas Lindsay, 1949- (CRC Press, 2013)
"Preface Kaizen means, simply, continuous improvement. It is based on the fundamentals of scientific analysis in which you analyze (take apart) the elements of a process or system to understand how it works so that you can learn how to influence it (make it better). Kaizen is the building block of all the Lean healthcare methodologies; it is the foundation upon which all of these methodshave been built. The small, gradual, incremental changes of continuous improvement applied over a long period add up to major positive impacts on patients' access to healthcare, patient safety, and the quality of medical results. Once your healthcare organization has committed to supporting a culture of continuous improvement, Kaizen workshops can be held periodically to make focused changes in the workplace. These workshops will take a magnifying glass, so to speak, to each process and every operation in the medical center in order to eliminate waste and improve services. This book was written to take you through the steps of conducting a very effective Kaizen workshop--one that is well planned, well implemented, and well monitored after said changes are implemented. The information is presented in a highly organized and easy-to-assimilate format. Numerous illustrations reinforce the text, and margin assists call your attention to key points and other important features. Throughout the book, you are asked to reflect on questions that will help you apply these concepts and techniques to your own workplace. Each chapter has a summary for quick review"--Vydavatelská anotace
Keywords: zdravotnický management; zdravotní péče; kaizen; ekonomická efektivnost; management jakosti; total quality management; health service management; medical care; economic efficiency; quality control; příručky; handbooks, manuals, etc